The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/nar/gky877
|View full text |Cite
|
Sign up to set email alerts
|

Nonfilament-forming RecA dimer catalyzes homologous joint formation

Abstract: Homologous recombination is essential to genome maintenance, and also to genome diversification. In virtually all organisms, homologous recombination depends on the RecA/Rad51-family recombinases, which catalyze ATP-dependent formation of homologous joints—critical intermediates in homologous recombination. RecA/Rad51 binds first to single-stranded (ss) DNA at a damaged site to form a spiral nucleoprotein filament, after which double-stranded (ds) DNA interacts with the filament to search for sequence homology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…Together these results lend further support to the idea that RecA2x is forming transient nuclei on ssDNA rather than stable filaments. 53 RecA WT and each of the constructs from RecA3x to RecA6x showed proficient RecA* filament formation as detected by a change in anisotropy at equilibrium. In comparing the results of RecA WT to the linked oligomeric constructs, the concentration-dependent filament formation curves appeared different.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Together these results lend further support to the idea that RecA2x is forming transient nuclei on ssDNA rather than stable filaments. 53 RecA WT and each of the constructs from RecA3x to RecA6x showed proficient RecA* filament formation as detected by a change in anisotropy at equilibrium. In comparing the results of RecA WT to the linked oligomeric constructs, the concentration-dependent filament formation curves appeared different.…”
Section: Resultsmentioning
confidence: 96%
“…Together these results lend further support to the idea that RecA2x is forming transient nuclei on ssDNA rather than stable filaments. 53…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea to extract single-particle information directly from individual electron micrograph images is not new (22,(36)(37)(38), but here we exploit geometric characteristics of polymeric systems to create an intuitive and reliable automated approach applicable to the growing, important class of beads-on-string systems (46)(47)(48). We show that the "functional form" of polymeric conformational properties in terms of bead-bead distances and three-bead angles, enabled adequate training based on only a few dozen manually picked oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…The size determined in this manner is slightly smaller than the sizes obtained by other methods, but is clearly larger than three bases. Recent analysis of a non-polymerizing RecA mutant showed that dimer formed by covalent linking can promote DNA pair formation while its monomer form cannot (Shinohara et al ., 2018). Since each RecA monomer covers three bases, this observation suggests that pair formation requires more than a three base match but less than a six base match, which is compatible with our results.…”
Section: A Recognition Size Of Five or Six Nucleotides Fits The Expermentioning
confidence: 99%